2002
DOI: 10.1159/000048648
|View full text |Cite
|
Sign up to set email alerts
|

Individual Quality of Life Factors Distinguishing Low-Burden and High-Burden Caregivers of Dementia Patients

Abstract: Dementia patient (n = 72) and caregiver characteristics and individual quality of life (IQoL) factors distinguishing low- and high-burden caregivers were evaluated. Measures included patient cognitive, functional and behavioural status, and caregiver burden, well-being, social support appraisal and IQoL. The caregivers were divided by median split into low- and high-burden groups. In the high-burden group daughters were over-represented, psychological morbidity was higher, QoL was lower, the patients were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 27 publications
8
58
1
4
Order By: Relevance
“…These findings are consistent with previous reports (Coen et al, 2002;Andrén and Elmståhl, 2007;Molyneux et al, 2008).…”
Section: Overall Burden and Differences Between Spouses And Adult Chisupporting
confidence: 94%
See 2 more Smart Citations
“…These findings are consistent with previous reports (Coen et al, 2002;Andrén and Elmståhl, 2007;Molyneux et al, 2008).…”
Section: Overall Burden and Differences Between Spouses And Adult Chisupporting
confidence: 94%
“…In line with that reported by numerous authors the analysis of specific factors revealed the important contribution to caregiver burden of the behavioural and psychological symptoms of patients (Fuh et al, 2001;Coen et al, 2002;Garre-Olmo et al, 2000), as well as that of functional disability (Garre-Olmo et al, 2002). These factors were distributed generally across both groups of caregivers, although the regression analysis indicated that they had a greater effect on spouses, probably due to their living in closer contact with the patient.…”
Section: Specific Factors Of Burden and Differences Between Spouses Asupporting
confidence: 81%
See 1 more Smart Citation
“…Focusing on hours of caregiving, the authors found a significant difference over the 6-month study period, with carers in the intervention group having more time to dedicate to activities unrelated to caregiving, which has potentially positive impacts on emotional well-being and QoL. 22,23 Therefore, more evidence is needed of the effectiveness and cost-effectiveness of interventions for supporting caregivers.…”
Section: Delivery Of Therapymentioning
confidence: 99%
“…In health related studies, it has been used in people suffering from peptic ulcer disease and irritable bowel disease (18), osteoarthritis (19), AIDS (20), cancer (21,22), cystic fibrosis (23), stroke (24), multiple sclerosis (17), mental illness (25), amyotrophic lateral sclerosis (26,27), people with leukaemia and lymphoma (28), people with End Stage Renal Failure (29), carers of people with dementia (30), and young people with diabetes (31) to name a few.…”
Section: Introductionmentioning
confidence: 99%